The role of green innovation on green restaurant patronage intention: urban vs. rural residents - Huang, Yun; Wei, Jingru; Wang, Kai; Hou, Qidi (Frontiers in Sustainable Food Systems, 2025)
IntroductionGreen restaurants minimize negative impacts on the environment through the implementation of green practices. Analyzing how urban and rural customers differ in their green consumption behaviors is necessary to get the whole society to support green eateries. This paper uses the theory of planned behavior with two extended predictors green innovation and anticipated regret, to explore whether there are differences in the factors that influence urban and rural residents' intention to patronize green restaurants.MethodsA questionnaire survey was conducted with 301 urban and 320 rural residents. The analysis was conducted using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 3.0 and multigroup analysis is employed.ResultsThe findings reveal signi?cant differences between the impacts of green innovation on the attitudes, the impacts of green innovation on behavioral intention, the impacts of subjective norms on behavioral intention, and the indirect effects of green innovation on the behavioral intention via attitudes for rural and urban residents. However, the results do not support any differences between the impacts of the attitudes, perceived behavioral control, anticipated regret on the behavioral intention for rural and urban residents.DiscussionThis study has enriched the relevant literature on green restaurant patronage from the perspective of comparing rural and urban residents, and can be used as a reference for the managers in implementing targeted strategies tailored to different residents for promoting green restaurant.